Interação entre fungos de solos e a formiga-cortadeira Atta sexdens (Linnaeus, 1758) - Nascimento, Mariela Otoni do (Universidade Federal do Tocantins, 2017)
The leaf-cutting ants (Hymenoptera: Formicidae), Atta and Acromyrmex genera, are the most important forest pests. They are found exclusively in Americas. Its economic importance is due to behavior to cut fresh plant material that serves as a substrate for the mutualistic symbiotic fungus Leucoagaricus gongylophorus (Basidiomycota: Agaricales) that are grown in underground chambers. Fertilized females are responsible for the founding of a new colony and they suffer direct influence of soil microorganisms. Therefore, newly fertilized females of Atta spp. should avoid fertile soils with high microbial load and even forested areas to found their nests. Entomopathogenic fungi and antagonists of L. gongylophorus are naturally present in the soil and they could be used in biological control of leaf-cutting ants. The objectives of this study were to evaluate and to compare the developing of young colonies of Atta sexdens in contact with soil from forested area and in contact with bare soils. Also, this and others procedures served to bioprospect antagonistic fungi of L. gongylophorus (Trichoderma spp.) from Gurupi region soil, and test the antagonistic effect of Trichoderma spp. against L. gongylophorus. In the first hours of start of experiments, Atta workers removed soil from colony recipients. This behavior could have favored colony survival, with a survival rate of 91,67 % during the 13 weeks. It was found that after the colonies have passed the critical period of foundation, the soil appears to exert little influence on the survival of workers and colonies. The soil from forested area had greater quantity and diversity of filamentous fungi than that from bare soil. The use of Tenebrio molitor as bait alive is efficient for bioprospecting by entomopathogenic fungi. All isolates of Trichoderma were able to inhibit in vitro growth of L. gongylophorus. Trichoderma spirale isolated 2 showed slow mycelial growth in Petri dish and strong level of inhibition against L. gongylophorus in vitro. So, this isolate is promising and should be tested in field.